Pengaruh Biaya Lingkungan, Leverage, dan Likuiditas Terhadap Profitabilitas Perusahaan Manufaktur - Kurniawan, Roykhan Dwi; Ismanto, Hadi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Manufacturing companies in Indonesia face challenges in maintaining a balance between compliance with environmental regulations and achieving profitability. Expenditures on environmental costs and debt-based funding structures can reduce corporate profits. Meanwhile, high liquidity does not necessarily have a direct impact on increasing profitability because it is not necessarily utilized productively. This study aims to analyze the effect of environmental costs, leverage, and liquidity on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021–2023. This study uses secondary data in the form of annual reports and sustainability reports obtained from the companies' official websites. The sample consisted of 51 companies with 153 observations selected using a purposive sampling method. Data were analyzed using panel data regression with a Fixed Effect Model (FEM) approach and robust standard errors. The results show that environmental costs have a significant negative effect on profitability (coefficient -0.0256; p = 0.000), and leverage also has a significant negative effect (coefficient -0.0050; p = 0.012). Liquidity has no significant effect on profitability (coefficient -0.0081; p = 0.420). These findings underscore the importance of efficiency in environmental cost management and a healthy financial structure to maintain sustainable profitability.